STUDY ON THE PRAWNS OF ASHTAMUDI BACKWATERS IN KERALA WITH SPECIAL REFERENCE TO PENAEIDS - Suseelan, C; Kathirvel, M (Indian Journal of Fisheries, 2011)
Fifteen species of prawns were recorded from Ashtamudi backwater systemwhicli included one species of sergesitid, five species of carideans and nine species ofpenaeids. The penaeid prawns were chiefly represented by juveniles of Penaeussemisulcatus, P., indicus, P. latisulcatus, Melapenaeus dobsoni and M. monoceros.While M dobsoni and P. indicus were the dominant species in most parts of thebackwaters, P. semisulcatus occurred more abundantly in some of the deeper areashaving relatively higher salinities (9.42-32.11% ). P. latisulcatus formed one ofthe common components of the catches taken during the post-monsoon period.Parapenaeopsis styltfera, the most dominant sepcies contributing to the marinefishery of this area, was encountered only in stray numbers.Commercial exploitation and population characteristics of the juvenilepenaeid prawns in these nursery areas are briefly discussed